Improving knowledge translation for increased engagement and impact in healthcare. Issue 3 (17th September 2020) - Eljiz, Kathy; Greenfield, David; Hogden, Anne; Taylor, Robyn; Siddiqui, Nazlee; Agaliotis, Maria; Milosavljevic, Marianna
Abstract : Ineffective knowledge dissemination contributes to clinical practice and service improvements not being realised. Meaningful knowledge translation can occur through the understanding and matching of appropriate communication mediums that are relevant for different stakeholders or audiences. To this end, we present a dissemination instrument, the 'REAch and Diffusion of health iMprovement Evidence' (README) checklist, for the communication of research findings, integrating both traditional and newer communication mediums. Additionally, we propose a 'Strategic Translation and Engagement Planning' (STEP) tool, for use when deciding which mediums to select. The STEP tool challenges the need for communicating complex and simple information against the desire for passive or active stakeholder interaction. Used collaboratively by academics and health professionals, README and STEP can promote co-production of research, subsequent diffusion of knowledge, and develop the capacity and skills of all stakeholders.